Bactrocera invadens (Diptera: Tephritidae), a new invasive fruit fly pest for the afrotropical region: host plant range and distribution in West and Central Africa - Goergen, Georg E.; Vayssières, Jean-François; Gnanvossou, D.; Tindo, M. (Oxford University Press, 2011)
In 2003, the invasive fruit ßy Bactrocera invadens Drew, Tsuruta & White (Diptera: Tephritidae) (Drew et al. 2005), of possible Sri Lankan origin, has been detected in the East and about 1 yr later in West Africa. In regular surveys in Benin and Cameroon covering 4 yr, samples from 117 plant species across 43 families have been obtained. Incubation of Þeld-collected fruits demonstrate that in West and Central Africa(WCA)B. invadens is highly polyphagous, infesting wild and cultivated fruits of at least 46 species from 23 plant families with guava (Psidium spp.), mango (Mangifera spp.), and citrus (spp.), and the wild hosts tropical almond (Terminalia catappa L.), African wild mango (Irvingia gabonensis (Aubry-Lecomte) Baill.), and sheanut (Vitellaria paradoxa C.F.Gaertn.) showing the highest infestation index. B. invadens occurs in 22 countries ofWCAwith new records for Angola, Central African Republic, the Congo, DR Congo, Equatorial Guinea, Gabon, Gambia, Guinea Bissau, Mali, Mauritania, Niger, and Sierra Leone. Overall, the pest has spread across a North-South distance of 5,000 km representing a contiguous area of 8.3 million km2 within WCA. B. invadens has adapted to a wide range of ecological and climatic conditions extending from low land rainforest to dry savanna. Because of its highly destructive and invasive potential, B. invadens poses a serious threat to horticulture in Africa if left uncontrolled. Moreover, the presence of this quarantine pest causes considerable restrictions on international trade of affected crops.